Promoting Women's Economic Empowerment : What Works? - Buvinic, Mayra; Furst-Nichols, Rebecca (World Bank Group, Washington, DC, 2014)
A review of rigorous evaluations of interventions that seek to empower women economically shows that the same class of interventions has significantly different outcomes depending on the client. Capital alone, as a small cash loan or grant, is not sufficient to grow women-owned subsistence-level firms. However, it can work if it is delivered in-kind to more successful women microentrepreneurs, and it should boost the performance of women's larger-sized SMEs. Very poor women need a more intensive package of services than do less poor women to break out of subsistence production and grow their businesses. What works for young women does not necessarily work for adult women. Skills training, job search assistance, internships, and wage subsidies increase the employment levels of adult women but do not raise wages. However, similar interventions increase young women's employability and earnings if social restrictions are not binding. Women who run subsistence-level firms face additional social constraints when compared to similar men, thus explaining the differences in the outcomes of some loans, grants, and training interventions that favor men. Social constraints may also play a role in explaining women's outcome gains that are short-lasting or emerge with a delay. The good news is that many of the additional constraints that women face can be overcome by simple, inexpensive adjustments in program design that lessen family and social pressures. These include providing capital in-kind or transacted through the privacy of a mobile phone and providing secure savings accounts to nudge women to keep the money in the business rather than to divert it to non-business uses.